A Community-Based Study on the Prevalence of Olfactory Dysfunction. Issue 5 (September 2020) - Schlosser, Rodney J.; Desiato, Vincent M.; Storck, Kristina A.; Nguyen, Shaun A.; Hill, Jonathan B.; Washington, Brandon J.; Noonan, Tegan E.; Lamira, Jensine; Mulligan, Jennifer K.; Rowan, Nicholas R.; Yoo, Frederick; Matthews, Lois J.; et al.
Background: Olfactory dysfunction (OD) is common, affecting an estimated 13 million adults in the United States. Prior studies may underestimate OD prevalence due to use of brief smell identification tests or age-adjusted cutoff values, which concede that it is acceptable for older people to have a decreased sense of smell. Objective: To determine OD prevalence in the healthy community when the goal and expectation is ideal olfactory function, rather than age-based population norms. Secondary goals were to explore factors associated with OD. Methods: Subjects without otolaryngic complaints were recruited from the community surrounding the Medical University of South Carolina. Olfactory-specific information was collected, and olfactory function was assessed using the Sniffin' Sticks test (Burghardt, Wedel, Germany) to measure threshold, discrimination, and identification (TDI). OD was defined as a TDI score < 31. Bivariate analysis and linear regression were used to determine factors associated with OD. Results: In total, 176 subjects were included with mean age of 52 years (range: 20–93), 111 (63%) female, and 127 (72%) white. Mean TDI score was 28.8 (6.9) and OD was present in 94 (53%) subjects. Multivariate linear regression revealed that TDI decreased an average of 1 point every 5 years. TDI was also associated with Mini-Mental Status Examination (MMSE) score, asthma, and gastroesophageal reflux disease. Threshold was associated with age, heart problems, and gastroesophageal reflux disease. Discrimination was associated with age and MMSE scores. Identification was associated with age, heart problems, and anxiety. Conclusions: In a community-based sample, OD affects greater than 50% of subjects. Aging impacts all aspects of olfaction, while the effects of factors such as asthma, MMSE scores, gastroesophageal reflux disease, heart problems, and anxiety may only be evident in specific olfactory subtests.